Pediatric donor management to optimize donor heart utilization. (21st March 2020) - Zimpfer, Daniel; Alexander, Peta M. A.; Davies, Ryan R.; Dipchand, Anne I.; Feingold, Brian; Joong, Anna; Lord, Karen; Kirk, Richard; Scales, Angie; Shih, Renata; Miera, Oliver
Abstract: Optimal management of pediatric cardiac donors is essential in order to maximize donor heart utilization and minimize the rate of discarded organs. This review was performed after a systematic literature review and gives a detailed overview on current practices and guidelines. The review focuses on optimal monitoring of pediatric donors, donor workup, hormonal replacement, and obliterating the adverse effects of brain death. The current evidence on catecholamine support and thyroid hormone replacement is also discussed. Recognizing and addressing this shall help in a standardized approach toward donor management and optimal utilization of pediatric heart donors organs.